Neutralizing Prejudices - Rúni Johannesen (Grounded Theory Review: An International Journal)
This study presents a social profile of a tolerant and global ideological behavior. The in-group-behavior revolves around enforcing the tolerant virtue and rooting out and eliminating prejudiced attitudes that affect minorities and the collective environment. The main concern is conceptualized as “enabling a nonjudgmental environment” for oneself and others. The recurrent solution to this concern is “neutralizing prejudices.” Neutralizing prejudices is a means to engage and deal with prejudiced oppression and prejudice-related behavior. Mindsets with a tolerant worldview use neutralization as a way to assert their worldview and cope with the prejudiced attitudes they experience towards minorities and the collective environment. Neutralizing prejudices is a way to negate, defuse, disqualify, or override a prejudiced context by applying an opposite or contrary force or effect. As such, neutralizing is mainly a rhetorical requisite. As a basic social process, neutralizing prejudices is a process of “collective regrouping” in relation to a social, moral, and global objective.